2012
DOI: 10.1002/jcop.21518
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Academic Outcomes Among Ghanaian Youth: The Role of Protective and Risk Factors

Abstract: Impoverished Ghanaian youth often experience minimal early learning opportunities and under‐funded, over‐crowded, and woefully inadequate schools. Female youth face even more formidable challenges as a result of sex stereotypes and other forms of gender discrimination in education. This combination of factors also predisposes them to significant risk for dropping out of school and reduces their chances to attaining postsecondary education. Using ecological theory and a risk and resilience framework, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…The results of the study differs from literature Laser, 2013); since the Bui study indicated that gender is not perceived to mediate CC for communities impacted by dams and associated resettlements. It also differs from studies by Liberman (1975), La Paro and Pianta (2000), and Clikeman-Semrud (2007, p.50), because for the Bui study the age of person is not perceived to influence CC available for people to overcome the impacts of dams and resettlements.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the study differs from literature Laser, 2013); since the Bui study indicated that gender is not perceived to mediate CC for communities impacted by dams and associated resettlements. It also differs from studies by Liberman (1975), La Paro and Pianta (2000), and Clikeman-Semrud (2007, p.50), because for the Bui study the age of person is not perceived to influence CC available for people to overcome the impacts of dams and resettlements.…”
Section: Discussioncontrasting
confidence: 99%
“…Men use more problem-focused coping than women at work and in situations having to be accepted and requiring more information but, not for emotion-focused coping (Folkman and Lazarus, 1980). Abukari and Laser (2013) argues that the Ghanaian youth often experience minimal early learning opportunities but, females are more negatively impacted through sex discrimination, and other forms of discrimination in education. In many cases, such discrimination comparatively predispose females to significant risks for dropping out of school and reduces their chances to attain postsecondary education.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Evidence of gendered psychological resources (e.g., agency, mastery and worth) in favour of males which may provide the requisite foundation to enable resilience characteristics (Shanahan and Hofer, 2005) have been supported by studies showing higher resilience in adolescent males compared to females (Campbell-Sills et al, 2009;von Soest et al, 2010;Waaktaar and Torgersen, 2012;Abukari and Laser, 2013;Stratta et al, 2013;Ying et al, 2014). Among older populations, males have also been found to report higher resilience (Boardman et al, 2008).…”
Section: Gender and Resiliencementioning
confidence: 99%
“…Simultaneously, there are concerns relating to how teachers and school systems can jeopardize resilience processes when these adults and institutions are prejudiced against girls (Cerise, Francavilla, Loiseau, & Tuccio, 2013). For example, Abukari and Laser (2013) documented that student-teacher relationships were inversely related to Ghanian girls’ academic success, possibly because of deeply entrenched expectations of girls’ incapacity for academic success. The results of the current study should, therefore, not be interpreted as proof that girls do not require continued teacher and school-based support.…”
Section: Discussionmentioning
confidence: 99%